EIB financing and borrowing activities 2020 - European Investment Bank (European Investment Bank, 2021)
In 2020, the European Investment Bank lent a total of EUR 66bn and the European Investment Fund committed close to EUR 13bn. To fund its activities, the EIB raised EUR equivalent of 70bn on the international capital markets. This report - previously called the EIB statistical report - provides in list form the projects financed and borrowings undertaken by the EIB, together with a list of the EIF's projects. It also includes summary tables for the year and over the last five years.